Dimensionality and Reliability of the Central Sensitization Inventory in a Pooled Multicountry Sample - Cuesta-Vargas, Antonio; Neblett, Randy; Chiarotto, Alessandro; Kregel, Jeroen; Nijs, Jo; van Wilgen, C Paul; Pitance, Laurent; Knezevic, Aleksandar; Gatchel, Robert J; Mayer, Tom G; Viti, Carlotta; Roldán-Jiménez, Cristina; et al. (J Pain, 2018)
Central sensitization (CS) involves the amplification of neural signaling within the central nervous system, which evokes pain hypersensitivity. The Central Sensitization Inventory (CSI) assesses 25 overlapping health-related symptom dimensions that have been reported to be associated with CS-related disorders. Previous studies have reported satisfactory test-retest reliability and internal consistency, but factor analyses have exhibited conflicting results in different language versions. The purpose of this cross-sectional study was to thoroughly examine the dimensionality and reliability of the CSI, with pooled data from 1,987 individuals, collected in several countries. The principal component analysis suggested that 1 general factor of CS best described the structure. A subsequent confirmatory factor analysis revealed that a bifactor model, which accounted for the covariance among CSI items, with regard to 1 general factor and 4 orthogonal factors, fit the CSI structure better than the unidimensional and the 4-factor models. Additional analyses indicated substantial reliability for the general factor (ie, Cronbach α = .92; ω = .95; and ω hierarchical = .89). Reliability results for the 4 specific factors were considered too low to be used for subscales. The results of this study clearly suggest that only total CSI scores should be used and reported.
Keywords: Dolor; Central Sensitization Inventory; Central sensitivity syndrome; Chronic pain; Psychometrics; Central sensitization; Multicountry sample